Aeolian-fluvial processes control landscape evolution along dunefield margins of the northwestern Negev (Israel) since the late Quaternary. (1st June 2022) - Robins, Lotem; Roskin, Joel; Yu, Lupeng; Bookman, Revital; Greenbaum, Noam
Abstract: Dunefield margins are sensitive to aeolian-fluvial processes that record local environmental conditions and climatic events. A common aeolian-fluvial process along dunefield margins is dune-damming—marking aeolian domination over a fluvial system. This study reports on the character, controls, and chronology of a transition from a pre-dunefield environment to a fluvial-dominated environment, at the intersection of the northwestern Negev desert (Israel) dunefield margins with a medium-sized (100 km 2 ) drainage basin. Relative and absolute Optically Stimulated Luminescence (POSL/OSL) dating along several radiocarbon dates and sedimentological analysis helped decipher the chronostratigraphy of nine sections in the drainage basin where it meets the dunefield, and reconstruct landscape evolution. The study reveals immediate and lagged fluvial response to aeolian domination during the Heinrich-1 and Younger-Dryas when the region was subject to exceptional wind power. The domination of vegetated linear dune encroachment over the drainage basin led to a temporal and spatial succession of dune-dammed waterbodies. Aeolian-dominated fluvial sedimentation resulted in a sequence of distinct event-based couplet depositions. Decreased wind power following the Younger-Dryas stabilized the properties of the dune-dams, while increasing fluvial activity during the early-Holocene, upon the stabilized dune-dams, led to aggregation of couplets in water bodies. These sediments formed the maximal extent of the dunefield margins alluvial plain. After the dune-dam breaching at the dunefield margins, fluvial penetration into the dunefield resulted in a mid-Holocene dune-damming impoundment within the dunefield. Altogether, the lagged fluvio-sedimentological response to aeolian-domination significantly contributed to the aggregation and extension of alluvial plains, shaping the dunefield margin landscape. Highlights: Late Pleistocene-early Holocene aeolian-fluvial dominated landscape evolution along dunefield margins. Sediment-based evidence of transition from aeolian to fluvial domination. Alluvial-plain formation along dune-field margins. Sedimentary units characterizing an aeolian-dominated environment. Dune-dam impoundment along the dunefield margins.